Developing a fluorescence‐coupled capillary electrophoresis based method to probe interactions between QDs and colorectal cancer targeting peptides. Issue 15 (27th May 2016) - Liu, Feifei; Wang, Jianhao; Yang, Li; Liu, Li; Ding, Shumin; Fu, Minli; Deng, Linhong; Gao, Li‐qian
Abstract : As is well known, quantum dots (QDs) have become valuable probes for cancer imaging. In particular, QD‐labeled targeting peptides are capable of identifying cancer or tumors cells. A new colorectal cancer targeting peptide, cyclo(1, 9)‐CTPSPFSHC, has strong targeting ability and also shows great potential in the identification and treatment of colon cancer. Herein, we synthesized a dual functional polypeptide, cyclo(1, 9)‐CTPSPFSHCD2 G2 DP9 G3 H6 (H6 ‐TCP), to investigate its interaction with QDs inside the capillary. Fluorescence‐coupled CE was adopted and applied to characterize the self‐assembly of H6 ‐TCP onto QDs. It was indicated that the formation of the assembly was affected by H6 ‐TCP/QD molar ratio and sampling time. This novel in‐capillary assay greatly reduced the sample consumption and the detection time, which was beneficial for the environment. It is expected that this kind of detection method could find more applications to provide more useful information for cancer diagnosis and detection of harm and hazardous substances/organisms in the environment in the future.